2018
DOI: 10.1177/0022427818787225
|View full text |Cite
|
Sign up to set email alerts
|

Mental Illness, the Media, and the Moral Politics of Mass Violence

Abstract: Objectives: We examine how news media portrays the causes of mass shootings for shooters of different races. Specifically, we explore whether White men are disproportionately framed as mentally ill, and what narratives media tend to invoke when covering mass shootings through the lens of mental illness as opposed to other explanatory frames. Methods: The study examines a unique data set of 433 news documents covering 219 mass shootings between January 1, 2013, and December 31, 2015. It analyzes the data using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 55 publications
(134 reference statements)
5
34
0
Order By: Relevance
“…This study is not immune from limitations. First, previous traditional media research efforts have shown significant bias in mass shooting media coverage based on event factors such as the race/ethnicity of both the shooter and the victims, as well as the number of associated casualties (Duxbury et al, 2018;Schildkraut et al, 2018). Guggenheim et al (2015) described the reciprocal relationship between traditional and social media discussing mass shooting events and we can assume the transference of this coverage bias.…”
Section: Resultsmentioning
confidence: 99%
“…This study is not immune from limitations. First, previous traditional media research efforts have shown significant bias in mass shooting media coverage based on event factors such as the race/ethnicity of both the shooter and the victims, as well as the number of associated casualties (Duxbury et al, 2018;Schildkraut et al, 2018). Guggenheim et al (2015) described the reciprocal relationship between traditional and social media discussing mass shooting events and we can assume the transference of this coverage bias.…”
Section: Resultsmentioning
confidence: 99%
“…Implicit or explicit racial biases can be central in people's understanding of social arXiv:1904.01596v2 [cs.CL] 4 Apr 2019 problems (Drakulich, 2015); in the mass shooting context, race is a factor in an event's newsworthiness (Schildkraut et al, 2018) and is often mentioned prominently in media coverage, particularly when the shooter is non-white (Mingus and Zopf, 2010;Park et al, 2012). Duxbury et al (2018) find that media representations of white shooters disproportionately divert blame by framing them as mentally ill while representations of non-white shooters are more frequently criminalized, highlighting histories of violent behavior.…”
Section: The Role Of the Shooter's Racementioning
confidence: 88%
“…A content analysis of news documents covering mass shootings from 2013 to 2015 found that white and Latinx male perpetrators were more likely to have their crimes attributed to mental illness than were shootings by black men. 41 White men were qualitatively described as more sympathetic characters than black and Latinx men, who were more often labeled as violent threats to public safety. 41 Despite the popular stereotype of mass shooters being white, statistically just over half (57%) of the perpetrators of FBI-defined mass shootings since the early 1980s have been white, and the majority of victims of mass shootings in recent years have been nonwhite individuals.…”
Section: An Agenda For Mental Health Research Into Mass Shootings Andmentioning
confidence: 99%
“… 41 White men were qualitatively described as more sympathetic characters than black and Latinx men, who were more often labeled as violent threats to public safety. 41 Despite the popular stereotype of mass shooters being white, statistically just over half (57%) of the perpetrators of FBI-defined mass shootings since the early 1980s have been white, and the majority of victims of mass shootings in recent years have been nonwhite individuals. 42 , 43 When a mass shooting occurs and the identified perpetrator is black, content analysis shows that politicians’ press briefings, media reports, and research articles rarely mention mental health and illness in descriptions of the perpetrator.…”
Section: An Agenda For Mental Health Research Into Mass Shootings Andmentioning
confidence: 99%